Terrorist Targeting, Information, and Secret Coalitions - Maurice Koster; Ines Lindner; Gordon McCormick; Guillermo Owen (Tinbergen Institute, 2010)
We consider a game played by a state sponsor of terrorism, a terrorist group, and the target of terrorist attacks. The sponsoring state wishes to see as much damage inflicted on the target of attack as possible, but wishes to avoid retaliation. To do so, his relationship with the terrorist group must remain ambiguous. The target of attack, for his part, wishes to bring these attacks to an end as quickly as possible and will consider the option of retaliating against the sponsor to do so. We approach the problem by introducing an “evidence” variable in a dynamic setting. We show that the interplay of different strategic and non-strategic effects boils down to three qualitatively different scenarios, determined by key parameters. Based on this result, two alternative instruments to retaliation are identified in order to resist terrorist activities. First, assuming that the target is able to change some parameters by monetary investments, the paper provides an economic analysis of how to invest optimally in order to make the sponsor lose incentives to support the terrorist group. Second, we propose changing the structure of the game. Here, the key insight is that the target country can make a unilateral statement as to his strategy. The sponsor cannot do so as he is in fact claiming that there is no cooperation with terrorist groups. While our discussion, in this article, is motivated by an important problem in contemporary counterterrorism policy, it applies more generally to the study of secret coalitions.
Keywords: C72; D82; 330; Secret Coalitions; Security Economics; Noncooperative Games; Terrorismus; Asymmetrische Information; Nichtkooperatives Spiel; Theorie